Classroom Management in Applying Android Applications as Learning Media in Online Learning: EFL Students’ Perceptions - Adolf Bastian; Vina Fathira (STAI Hubbulwathan Duri, 2022)
English pronunciation should be taught effectively during pandemic in online learning. In classroom management, android application as learning media is one of the solutions in classroom management to help the learners practice pronunciation in English Phonology class. This study can help teachers evaluate classroom management for future learning in EFL during the Covid-19 pandemic for English pronunciation issues more accurately than before. This study aims at investigating EFL students’ perception of classroom management in online learning in the English pronunciation class during the covid-19 pandemic by applying android application as learning media. The method of the research was descriptively quantitative. The sample of this research was 34 students. The instrument for this research was a set of questionnaire of 20 questions delivering to the students by Google form. After getting the data based on the students’ answer in questionnaire, the data was analysed. The data analyzed by counting the percentage of each option of four, and give description on it. The result of the research stated that the students’ perception about classroom management in applying android application as learning in online learning was very helpful since it supported the students’ learning while using android application. However, only a few student was saying not helping them because this application only available in android mobile phone not in the IOS. The conclusion of the research was the students’ perception in classroom management in online learning was helpful themselves to learn English pronunciation by applying android application.